Multivariate regression analysis of disinfection kinetics using Moringa oleifera defatted seed extract - Idris, Munirat Abolore; Hammed, Ademola Monsur; Jami, Mohammed Saedi; Jamal, Parveen (Asian Research Publishing Network (ARPN), 2017)
The objective of this research is to determine the disinfection inactivation kinetics of defatted Moringa oleifera salt seed extract on Escherichia coli (E.coli) bacterial strains using statistical multivariate regression analysis. The disinfection kinetics of the seed extract was carried out using a batch mode treatment of water in shake flasks and the bacterial count of E.coli bacterial cells were used as microbial indicators. The order of reaction as well as the models of different disinfection kinetics were determined. The goodness of fit for each model studied were evaluated using regression analysis in SPSS. The results revealed that modified Homs model better describes the disinfection inactivation kinetics for defatted moringa oleifera seed salt extract and the extract deviated from first order reaction. this is the first study on modified Hom’s law to describe the inactivation of E.coli using defatted Moringa oleifera seed salt extract.